Physiological responses during submaximal interval swimming training: effects of interval duration - Bentley, D. J.; Roels, B.; Hellard, P.; Fauquet, C.; Libicz, S.; Millet, G. P. (Journal of Science and Medicine in Sport, 2005)
The aim of the present study was to determine the time sustained near VO2max in two interval training (IT) swimming sessions comprising 4x400 m (IT(4x400)) or 16x100 (IT(16xl00)). Elite swimmers (Mean+/-SD age 18+/-2 yrs; body mass 66.9+/-6.5 kg: swim VO2max 55.7+/-5.8 ml.kg(-1).min(-1)) completed three experimental sessions at a 50-m indoor pool over a one week period. The first test comprised a 5 x 200-m incremental test to exhaustion for determination of the pulmonary ventilation threshold (VT, m.s(-1)), VO2max, the velocity associated with VO2max (VO2max, m(s(-1)) and maximum heart rate (HR(max), b.min(-1)). The remaining two tests involved the IT(4x400) and IT(16xl00) performed in a randomised order. The two IT sessions where completed at a velocity representing 25% of the difference between the VT and the VO2max (delta25%) and in the same work to rest ratio. During the IT sessions VO2 as well as HR were measured. The duration (s) >90% VO2max, also the duration (s) >90% HR(max), were not significantly different in the IT(16x100) and IT(4x400). However, limits of agreement (LIM(AG)) analysis demonstrated considerable individual variation in the time >90% VO2max (mean difference +/-2SD = 222+/-819 s) and the time >90% HRmax (mean difference +/-2SD = 61+/-758 s) between the two IT sessions. This factor deserves further research to establish the characteristics of those athletes which influence the physiological responses in IT of short or longer duration repetitions.